Penilaian Kualitas Aplikasi Akuntansiku: Mengukur Kepuasan Pengguna Melalui Model Dromey - Dom Noel Wijaya, Johanes; Kisnanto, Adi; Rizky Wicaksono, Soetam (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
The rapid development of information technology has increased the demand for reliable software, especially in the accounting field. The Akuntansiku application is one of the accounting software solutions designed to assist small and medium-sized enterprises (SMEs) in financial management. This study aims to assess the quality of the Akuntansiku software using the Dromey model, which measures aspects such as correctness, efficiency, integrity, and usability of the application. The Dromey method links high-level quality characteristics with concrete, measurable software elements. The results of the study indicate that the Akuntansiku application has good quality in terms of information reliability and ease of use, but there are several aspects that require improvement, especially in memory efficiency and the development of interactive features. This research is expected to provide insights for developers to improve the quality of the system and offer guidance for users in selecting accounting software that meets the desired quality standards.